A Qualitative Study: Chinese Cancer Caregivers in Sarawak - Cheong, Rina RN; Zabidah, Putit (Malaysian Nurses Association, 2011)
This qualitative research explores the experience of cancer caregivers in Sarawak. What are the impacts of cancer to the patient’s family members? How did they cope when their relatives were first diagnosed having cancer? What are the coping styles that work for the family while a relative underwent treatment? How could the nurses help and assist the patient and relative while in these states of mind. In this study data were collected from interviews with nine Chinese cancer caregivers. Data obtained were analyzed to gather and capture the experiences of Chinese cancer caregivers. Various themes emerged from the data and highlighted in this paper. These includes “Why me?”, Sadness, Acceptance of the Reality, Difficulties Faced by the Caregivers, Family Conflicts, Blames, Suffering, Remembering the Loss, Coping Mechanisms, Supports, Contact with Nurses. Cancer poses great emotional distress and difficulties to the family, in particular those who provide care for their loved ones. The findings of this study emphasized that the provisions of supportive care from the nurses help to alleviate psychological and emotional suffering of caregivers during this intricate time. The oncology nurses can express empathy through recognizing and accepting caregivers’ values and beliefs.